Do Gen Z buy Cosmetics using Augmented Reality Impulsively? A Deep Learning-Based SEM-ANN Analysis - Anish Kaushal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Social media marketing is effective tools in relation to Generation Z’s impulse purchasing behaviour within fashion industry in the context of cosmetics purchase. However, there is research gap on mediating roles of media types and ease of payments on social platforms in awakening the interest of Gen Z females and moderating roles of virtual reality (VR). SEM-ANN was conducted based on 287 valid responses. The findings reveal that media can trigger a stronger urge to buy impulsively and impulse buying intention. Moreover, the awakening of interest and ease of payment options plays mediating roles in this process. Secondly, with the recent advancements of virtual reality (VR) technologies, VR applications in cosmetics are increasingly becoming an inevitable trend of future shopping. The empirical results show that media types and ease of payments results in creating urge to impulsive purchase behaviour. Furthermore, the role of AR and VR strengthens the impulsiveness trait in driving the urge to buy impulsively.